2006
DOI: 10.1097/00129689-200604000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Gastroplasty in Esophagectomy for Esophageal Cancer: A Comparative Study

Abstract: How best to approach esophagectomy is a controversial issue. In the last decade, the opportunity to use minimally invasive surgical methods for esophagectomy has been documented, but their real advantages over conventional surgery have yet to be clearly established. The aim of this study was to compare a series of patients who underwent laparoscopic esophagectomy with those who underwent open surgery to ascertain the feasibility, safety, and clinical advantages of the former surgical techniques. Between Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The main criteria for trial exclusion included reviews, double publications, different primary outcomes, and non-comparative studies [15][16][17][18]26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main criteria for trial exclusion included reviews, double publications, different primary outcomes, and non-comparative studies [15][16][17][18]26].…”
Section: Resultsmentioning
confidence: 99%
“…Using the electronic databases Medline, Embase, Pubmed and the Cochrane Library, we identified all English language comparative studies from 1997 to 2009 that involved minimally invasive versus open esophagectomy [7][8][9][10][11][12][13][14][15][16][17][18]. A combination of the following search terms were used: randomized controlled trials, comparative study, esophagectomy, minimally invasive surgery, open transhiatal, VATS, thoracoscopy, laparoscopic transhiatal, gastric conduit, thoracotomy and esophageal cancer.…”
Section: Literature Searchmentioning
confidence: 99%
“…Seven series [25][26][27][28][29][30][31] directly compared open oesophagectomy versus MIO; two of these [27,28] were performed prospectively. Review of 30 of the identified papers revealed three main groups of common outcome measures: operative data, morbidity and mortality data, and oncological resection data.…”
Section: Resultsmentioning
confidence: 99%
“…In the last two cases treated, the reconstruction was done using a laparoscopic technique for the mobilization and transposition of the stomach. This approach was borrowed from our experience with cancer patients with a view to reducing the surgical trauma [33]. The choice of the route for gastric tubule transposition cannot be standardized in delayed reconstruction.…”
Section: Discussionmentioning
confidence: 99%